The reliability and sensitivity of the sub-maximal yo-yo intermittent recovery test during a 6-week pre-season - Keehne, P.; Wright, J.; Neville, C.; Bruce-Low, S. (Sport Performance & Science Reports, 2022)
The Yo-Yo Intermittent Recovery - Level 1 (IR1) test is frequently used within professional soccer for the eval uation of a player`s physical performance; however, it`s ex haustive nature often limits the frequency of testing and the implementation of test results to coaching sessions. In re placement, it is suggested the sub-maximal 6-min Yo-Yo IR1 (Yo-Yo IR1sub) is more appropriate for routine testing, with much less impact on coaching planning and delivery. Previous research has demonstrated that the heart rate (HR) responses in the final minute of the Yo-Yo IR1sub are strongly correlated (r = -0.74) to a player`s relative maximum HR (%HRmax) (1). More recently, Owen et al. (2) and Doncaster et al.(3), concluded absolute HR taken in the final minute of the Yo Yo IR1sub provides a practical alternative to the Yo-Yo IR1, due to good levels of reliability (CV = 1.1-1.6%). There is, however, a lack of research focused on the sensitivity of the Yo-Yo IR1sub to detect change across a soccer mesocycle (e.g., pre-season).